Titanium dioxide coating microfiber for humidity sensor application / Syed Mohammad Ammar Haeder - Syed Mohammad Ammar , Haeder (2019)
In this project, the effects of Titanium dioxide coating and fiber diameter on the performance of optical fiber humidity sensor were investigated. To start off, each fiber is tapered with the help of flame brushing on the waist region in order to reduce the fiber diameter. Then, each tapered fiber is sealed in a humidity chamber with RH increased from 45% to 90% and the power output against this change is noted. In the first experiment, the 7 μm coated sample was compared with a 7 μm non-coated sample to see the effects the titanium dioxide coat brings. The coated sample showed displayed better performance as it showed greater sensitivity and greater linearity. For the second experiment, three diameters 3 μm, 7 μm and 10 μm respectively and all coated with titanium dioxide in order to check the result of varying diameter on sensor performance. The smallest diameter (3 μm) was found to show greatest sensitivity and linearity, followed by 7 μm whereas the 10 μm had the least numbers of the three. Hence, the 3 μm sample was considered as ideal choice as a RH sensor.